Strategic Pragmatist Analysis of Saudi Arabia and the UAE through Diplomatic Normalization with Israel - Ainul Ismah; Jesha Yemima Gunawan; Monica Indah Winarno; Yulia Rimapradesi (Inovasi Saintific Review, 2025)
This research employs a qualitative approach with a comparative case study method as a means to analyze the forms of pragmatic foreign policy strategies of Saudi Arabia and the United Arab Emirates (UAE) in their processes of diplomatic normalization with Israel. According to Yin (Yin, 2018), the comparative case study method is suitable for understanding contemporary phenomena within real-life contexts and allows for an in-depth analysis of the strategic differences between actors. Data were collected through literature studies, including official policy documents, diplomatic statements, the Abraham Accords (2020), reports from international organizations, academic journals, and credible media articles. This research utilizes FPA (Foreign Policy Analysis) (Hudson, 2005) and content analysis methods to identify strategic motives, political narratives, and national interests in the process of diplomatic normalization. Furthermore, thematic comparison techniques are employed to assess the similarities and differences in the patterns of Saudi and UAE pragmatism, particularly in terms of economic, security, geopolitical, and domestic dynamics. Data validity is strengthened through source triangulation and cross-verification between primary data (such as official documents) and secondary data from academic literature and expert analyses.